The effects of inhibition on linguistic ability in eastern societies. - Tang, Natalie. (2012)
Inhibitory control is defined as the ability to supress instinctive, immediate, dominant responses. Rapid development of inhibitory control occurs during the preschool ages, and this cognitive skill has been found to predict measures of language achievement in terms of reading and writing ability. The current study aimed to extend this finding in a population of Singaporean preschoolers (N = 69) aged 40 to 71 months by evaluating the predictive value of inhibitory control on other tests of language achievement, namely verbal and listening ability. The Go-Nogo test was employed to evaluate inhibitory control, and four sub-tests from the Woodcock-Johnson III Tests of Achievement were used to measure these linguistic abilities. Scores obtained on these four sub-tests were then combined to form a general linguistic ability index. Performance on the Go-Nogo test of inhibitory control was found to significantly predict this index. Additionally, significant age effects were found across this linguistic ability index. The practical implications of these findings within the context of an Asian society are discussed, as well as the impact of the lack of adequate batteries and norms for testing in such societies.